IMPLEMENTASI KEBIJAKAN TATA KERJA PANGKALAN PENJAGAAN LAUT DAN PANTAI KELAS II BITUNG - Rengga, Joseph; HS Tangkau, Charles; Bogar, Wilson (SEIKO : Journal of Management & Business, 2020)
The purpose of this research is to describe, analyze, and interpret the implementation of the Organization and Work Procedure of Class II Bitung Sea and Coast Guard Base. This type of research is Qualitative. The reason for using this research is because of the appropriateness of the existing problems in which to understand the implementation of the policies of the Organization and Work Procedure of the Marine and Coastal Base at PLP Class II Bitung in North Sulawesi Province, natural and natural holistic are needed in order to obtain data from the problem in depth (Verstehen). The results of the study show that: Enforcement of authority from the KPLP refers to article 278 of Law Number 17 Year 2008 concerning Shipping, namely the problem for enforcement of ships with foreign flags which tends to be rather difficult because of the Flag State, according to the provisions of officers must coordinate first with the flag's country of origin because when the flag is located it is likened to a running country. Regarding the application of sanctions when incomplete vessel documents are found when carrying out shipping safety supervision operations, they are still not firmly applied to the maximum. From the data found there are vessels whose documents do not exist or have expired / the operating permit period has expired; The ship departed without a sailing agreement; There has never been a shipping crime handled by PPNS that can reach the court. Keywords: Public Policy, Policy Implementation, Law Number 17 Year 2008 concerning Shipping in KPLP Bitung